Prime Fuzzy Submodules and Quasi Primary Fuzzy Submodules - Hadi, Rabee (University of Thi-Qar Journal of Science, 2008)
In this paper we give some results about fuzzy quasi prime submodules,also,we study the notion of quasi primary fuzzy submodules